Exploring the need for Academic Support Programmes (ASPs) for returning undergraduates at Rhodes University - Matabane, Ramathetse Belinda (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
The overarching purpose of this thesis is to explore the need for Academic Support Programmes (ASPs) in higher education with specific reference to returning undergraduates in the Sociology Department at Rhodes University. The transformational agenda in higher education in post-apartheid South Africa in terms of expanding access to education, the promotion of accountability and efficiency in higher education, massification, the articulation gap between school and university, institutional culture, unpreparedness of universities and underpreparedness of students comprise the conceptual core of this study. I undertake to investigate the necessity and relevance of academic support offered to returning undergraduates at Rhodes University. I do this by exploring two main issues theoretically and in my fieldwork. The two main issues that form the basis of this research are students' perceptions regarding availability and accessibility of academic support programmes in the Sociology Department and students' perceived academic needs. Students' perceptions and attitudes towards Academic Support Programmes have been uncovered through both quantitative and qualitative fieldwork to gauge the extent to which literature is applicable when it comes to the above-mentioned conceptual frameworks. The study illustrated that academic support is not exclusive to first year students. It is also clear that improved, systematic academic support gives rise to improved student academic performance. Throughout the study, students perceive availability and accessibility of ASPs as a challenge.
Keywords: Compensatory education -- South Africa -- Makhanda; Rhodes University. Department of Sociology